2007
DOI: 10.2353/ajpath.2007.061042
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Effects of the Nuclear Factor κB Subunit p50 on Myocardial Ischemia-Reperfusion Injury

Abstract: Nuclear factor B (NF-B) is a ubiquitous transcription factor activated by various stimuli implicated in ischemia-reperfusion injury. However, the role of NF-B in cardiac ischemia-reperfusion injury has not yet been well defined. Therefore, we investigated reperfusion damage in mice with targeted deletion of the NF-B subunit p50. Electrophoretic mobility shift assays validated NF-B activation in wild-type (WT) but not p50 knockout (KO) mice. KO and WT animals underwent 30 minutes of coronary artery ligation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 33 publications
2
42
1
2
Order By: Relevance
“…In addition, Frantz et al also reported that the reduction of cardiac ischemia/reperfusion injury in p50-deficient mice was abolished with transplantation of bone marrow cells isolated from wild-type mice, indicating that the primary mechanism of injury is activation of NF-B in infiltrating leukocytes and not in cardiomyocytes. 22 Taken together, these observations suggest that p50-deficient mice may not be the appropriate model to clarify the role of the NF-B pathway in cardiomyocytes. Thus, we used cardiomyocyte-specific IKK␤-deficient mice in this study.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, Frantz et al also reported that the reduction of cardiac ischemia/reperfusion injury in p50-deficient mice was abolished with transplantation of bone marrow cells isolated from wild-type mice, indicating that the primary mechanism of injury is activation of NF-B in infiltrating leukocytes and not in cardiomyocytes. 22 Taken together, these observations suggest that p50-deficient mice may not be the appropriate model to clarify the role of the NF-B pathway in cardiomyocytes. Thus, we used cardiomyocyte-specific IKK␤-deficient mice in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Esta mayor traslocación del factor de transcripción fue coincidente con el aumento de la subunidad p50 en núcleos y con la expresión incrementada del ARNm de iNOS. También es importante destacar que está ampliamente demostrado que el incremento de la síntesis de óxido nítrico, produce peroxinitrito, un radical que se ha postulado como uno de los mayores responsables en la muerte celular en este tipo de tejido esquelético 33 . En todas estas investigaciones además se pone de manifiesto que un aumento en los niveles de inflamación incrementa el daño celular en el tejido cardiaco.…”
Section: Discussionunclassified
“…The severity of myocardial damage is related to the degree of infection (25,26). Pharmacological inhibition or targeted deletion of elements of inflammatory mediators has been proven to be effective in reducing infarction, improving myocardial function and survival (27)(28)(29)(30). Pro-inflammatory cytokines are known to stimulate the formation of reactive oxygen species, which in turn amplify the inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%